Good enough : a cookbook : embracing the joys of imperfection & practicing self-care in the kitchen - Brown, Leanne (Workman Publishing, 2022)
"Good enough is a cookbook, but it's as much about the healing process of cooking as it is about delicious recipes. It's about acknowledging the fears and anxieties many of us have when we get in the kitchen, then learning to let them go in the sensory experience of working with food. It's about slowing down, honoring the beautiful act of feeding yourself and your loved ones, and releasing the worries about whether what you've made is good enough. It is. A generous mix of essays, stories, and nearly 100 dazzling recipes, Good Enough is a deeply personal cookbook."--Back cover.